Identifying the monotonic trend in climate change parameter in Kluang and Senai, Johor, Malaysia - Firdaus Mohamad Hamzah,; Farahani Mohd Saimi,; Othman Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Presently, climate change plays an important role as it gives a serious impact to the living things on earth. Analyzing the trend of climate change is very important in identifying the pattern of changes because it can give an initial overview for future analysis. In this study, trend analysis was carried out to study the pattern of changes for five climate change parameters, such as total amount of monthly precipitation (mm), monthly average temperature (°C), monthly average global radiation (MJm–2), monthly average wind speed (m/s) and monthly average humidity (%) during the period of 1974 to 2010. Comparisons were made between two research stations, which were the Senai International Airport and Kluang Meteorological Stations. In this study, the Mann-Kendall trend test and Sen’s slope estimator test were used to identify the monotonic trend for these climate change parameters. As a result of this analysis, the precipitations showed no trend for both locations and the radiation showed no trend in Kluang from both analyses. Meanwhile, other parameters in Senai and Kluang showed a monotonic trend, according to the Tau value (Z) and the Sen’s slope value. The temperature shows a positive trend for both locations.